Epilepsy, literature and linguistics: spotlighting subjective symptoms - Sanchez-Davies, Jennifer (BMJ Publishing Group, 2018)
Literature can offer a wealth of information about epilepsy: from complex narratives to children’s picture books, it can help broaden people’s understanding, show what it is like to live with epilepsy, and provide a medium to which people with epilepsy can relate. The latter being particularly important in such cases where seizure experiences are highly subjective, such as those associated with ‘focal seizures’, a common seizure type, which are known for their variable and hard-to-describe symptoms, causing complications with diagnosis as many of the symptoms overlap with those of other psychological health conditions. Literature, however, has more to offer than acting as a source for demystifying epilepsy. On a disciplinary level, literature is surrounded by different frameworks for linguistic analysis which, importantly, are also applicable to real-life discourse. In particular, the well-established discipline, cognitive stylistics, provides ample theory for analysing the different facets of literature, from narratological and storyworld level, to the intricacies of characterisation revealing the structure behind the presentation of fictional characters’ experiences, attitudes and personalities. Such methods have the potential to transform and decode complex, subjective experiences into manageable pieces of information. This, then, holds great potential for shedding light on the experiences of real-life seizure narratives to the extent that the identified seizure’s linguistic ‘profiles’ can be used to aid real-life situations. Therefore, the present study calls to attention the potential evoked through the convergence between literature, linguistic analysis, fictional characters, PWE, and seizure narratives. Extrapolating the qualities of these converging strands can enrich our understanding of the seizure experience as well as bring to awareness the areas of risk that surround aspects of the diagnosis process.